Human dental pulp stem cells differentiation into odontoblast and osteoblast-like cells on scaffolds contain bioactive materials: Human dental pulp Stem cells differentiation - Ghawtha Khudhur, Ganjo; Khalid Bakr, Diyar (Cellular and Molecular Biology, 2024)
Epigenetic change has been found to play an important role in cell differentiation and regulation and the dental pulp stem cell in tissue engineering is gaining attention due to the ability of cells to differentiate into odontoblast and other cells. This study evaluated the influence of poly L- lactic acid with hydroxyapatite-coated with polyaniline scaffold (PLLA/HA/PANI) on dental pulp stem cell (DPSC) proliferation and differentiation. After scaffold preparation and DPSCs seeding, the cells proliferation and differentiation were evaluated by immunocytochemistry assay and cell viability was measured by cytotoxicity / MTT assay. The results showed (PLLA/HA/PANI) scaffold facilitates DPSC proliferation and differentiation with gene expression. This finding underscores the promise of this biomaterial combination as a scaffold for dental tissue regeneration and application.